Agricultoras familiares: o conhecimento que brota na horta e a comercialização direta dos alimentos - Silva, Jossiane Ortiz (2021)
This qualitative research objective to identify what drives women to produce and sell food, verifying how the technical, productive, economic and sociocultural dimensions interfere in their choices. The study went through three phases: 1) exploratory phase; 2) Field work; 3) Analysis and treatment of empirical and documentary material. The categorization of the data took place according to the dimensions of agroecology and the guiding questions: technical-productive (how the decision-making process about what will be planted, how it will be planted and which foods will be marketed), economic (verification if the production and the fair allowed autonomy in relation to income), and sociocultural (data on education, identity and information and communication technology). It was found that the main aspect that leads to the commercialization and production of food is the concern with health and the intention to offer consumers a healthy food. This supports the fact that the predominance of agroecological and organic systems was found, respectively, in the cases studied. As for the forms of decision making, one case that tends to the autocratic form was verified, and eight cases in which decisions have a shared character. Regarding the economic participation of women in the composition of family income (since they entered the fair), it was possible to verify that there was an increase (although difficult to measure, as it was not possible to obtain records of these data). However, it was alleged that it led to an improvement in the living conditions of farmers, enabling access to services and products, such as the internet and family outings. However, it was evident that fair income is secondary in terms of family income composition as pensions are relevant in most cases. It should be noted, as the workforce, the predominance of family labor, with overload and accumulation of tasks in the case of women. As for the sociocultural aspects and their influence on the commercialization process, it can be seen that the food produced was already part of their childhood, what has changed is that the production now intended for the subsistence of the family is now commercialized. Thus, it was possible to see that popular knowledge is rooted in these women, and is part of the decisions about what, when and how to produce. Regarding the level of education, it can be observed that it is very diverse, which made it difficult to draw a profile of female farmers. As for the forms of communication, which is essentially direct (due to the form of face-to-face marketing), the importance of using the WhatsApp application and the fact that more than half of the farmers mention that they use digital means to do adverts. The entire process that takes place until arriving at the fair, the decision-making, production, what to take, everything makes up a cycle, thus, in these cases, there is no way to separate the production/marketing binomial. The interconnections between production and direct marketing, together with the relationships built between producers and customers, are fundamental components of a reciprocal learning process. You learn to produce and consume a diverse menu of foods, that is, you learn to plant and eat the color on your plate.